EFFECTS OF CYTOKININ TYPES AND THEIR CONCENTRATIONS ON CALLUS FORMATION FROM DIFFERENT SOURCES EXPLANTS OF SARANG SEMUT PLANT (Myrmecodiatuberosa Jack.) - Yanti Puspita Sari; Wawan Kustiawan; Sukartiningsih -; Umrah - (PROSIDING SEMINAR KIMIA, 2015)
This study aim was to determine the influence of types and different concentration of cytokinin on the callus formation. The different sources of explant (cotyledons, stems, tubers, roots) from sarangsemut plants was cultured in Murashige-Skoog medium, supplemented with various levels of 2.4 Dichlorophenoxy Acetic Acid (2.4 D)viz0.5; 1; 1.5; 2 mg/l and combined with 2mg/l kinetin were performed to investigate callus formation. The results showed that the best callus formation was found on medium-supplemented with 2 mg/l 2,4-D and 2 mg /1 Kinetin on four sources of explant used. In addition, phenolic, alkaloids, flavonoids, tannins and steroids were also present in the callus.